(untitled) (London Journal of Medical and Health Research, 2026)
Glioblastoma (GBM) is one of the most aggressive and difficult-to-treat tumors in humans. The low efficacy of treatment is due to the molecular and cellular heterogeneity of the tumor, as well as disruption of biochemical mechanisms of the innate immune system, including peptides such as cathelicidin LL-37 and protegrin-1 (PG-1). The objective: to establish the effect of the combined use of LL-37, PG-1 and chemotherapy drugs on the expression of p53, GFAP, ATRX, Ki-67, TF, PDPN and EGFR proteins in GBM patient cell cultures, as well as their relationship to overall survival (OS) and life expectancy (LE) of patients. Materials and Methods: Cells were isolated from GBM biopsies obtained from patients (n = 30) and grown under standard conditions for 2 days. The cells were treated with different doses of the following chemotherapy drugs: temozolomide (TMZ), doxorubicin (DOX), carboplatin (CARB), cisplatin (CIS), etoposide (ETO) as well as peptides LL-37, PG-1, to determine the 50% inhibitory concentration (IC50) using the MTT assay. The expression of p53, isocitrate dehydrogenase-1 (IDH1), glial fibrillary acidic protein (GFAP), ATP helicase chromatin (ATRX), proliferation antigen (Ki-67), transferrin (TF), podoplanin (PDPN), and epidermal growth factor receptor (EGFR) proteins in GBM cells analyzed using immunohistochemical (ICH) staining with specific antibodies. Associations between these proteins and OS were analyzed using GraphPad Prism 8.0 software. Results: Statistically significant correlations were found between the expression of TF (r= -0.556, p=0.04), EGFR (r=0.799, p=0.03) and Ki-67 (r= 0.651 p=0.002) and TF (r=-0.899, p=0.004) in GBM cells and the IC50 values of LL-37, PG-1 respectively. The low IC50 value of LL-37 (less than 7 μM) and the high expression of p53 protein (20%, 12 vs 6.5 months, p=0.0037), GFAP (40%, 12 vs 9 months, p=0.0019) were associated with a longer life expectancy for the patients. In contrast, low sensitivity of GBM cells to LL-37 (higher 7 μM) and high expression of Ki-67 (15% or higher) were associated with a shorter life expectancy for the patients (10 vs 14 months, p=0.0452). Conversely, low EGFR expression (below 40%) and a low IC50 for LL-37 were associated with a longer life expectancy (12 vs 6.5 months, p=0.0031). High sensitivity of GBM cells to PG-1 (less than 8 µM) and high expression of proteins p53 (20%, 12 vs 8 months, p=0.0126), GFAP (40%, 24 vs 10 months, p=0.0042), ATRX (higher 15%, 8 vs 14 months, p=0.0346), as well as low expression of Ki-67 (below 15%, 8 vs 14 months, p=0.0346) and EGFR (below 40%, 8 vs 12 months, p=0.0124) were associated with an increase life expectancy. Low EGFR expression (below 40%) and low sensitivity to PG-1 were associated with longer life expectancy (12 vs 8 months, p=0.0124). Conclusions: The observed associations between the expression of p53, GFAP, Ki-67, and EGFR proteins in GBM cells, as well as ATRX expression and IC50 of LL-37 and PG-1 with OS of the patients may potentially be used to develop a chemoimmunotherapeutic scheme for evaluating the efficacy of treatment in GBM patients.